Detecting Fraudulent in Financial Statements Using Fraud Pentagon: Analysis of Banking Companies in Indonesia and Thailand - Putri, Maya Eky Antoko; Setiyorini, Wahyu (Jurnal Akuntansi dan Perpajakan, 2024)
This study aims to analyze the effect of fraud pentagon theory on detecting fraudulent financial statements. Fraud pentagon theory consist of five variables namely pressure, opportunity, rationalization, capability, and arrogance. The sample is banking companies listed on Indonesian and Thailand Stock ExchangeÂ  with a total of 174 samples companies. The observation period is 3 years during 2020-2022 period. The analysis technique is logistic regression analysis. The results of the analysis in Indonesian banking companies show that only variable capability has significant effect on fraudulent financial statements, while other variables namely pressure, opportunity, rationalization, and arrogance have no significant effect on fraudulent financial statements. The results of the analysis in Thailand banking companies show that only variable pressure has significant effect on fraudulent financial statements, while other variables namely opportunity, rationalization, capability, and arrogance have no significant effect on fraudulent financial statements.